Meta Analisis Pengaruh Lembar Kerja Siswa Berbasis Virtual Laboratory terhadap Hasil Belajar Fisika Peserta Didik - Putri Fathiya Artha Dewi; Irnin Agustina Dwi Astuti; Mamik Suendarti (Pendidikan Fisika Universitas Nurul Huda, 2023)
The implementation of the physical distancing policy causes learning to be carried out online by changing the learning pattern in class and practicum in the laboratory or field to virtual or independent practicum activities. The purpose of this study is to determine the magnitude of the influence of virtual laboratory-based Student Worksheets (LKS) on the overall physics learning outcomes of students based on related variables and to determine the magnitude of the influence of virtual laboratory-based LKS on physics learning outcomes based on education levels. The research method used in this study is meta-analysis, namely narrative review and systematic review by analyzing the results of research that has been published nationally related to the use of virtual laboratory-based LKS on physics learning outcomes. Overall, virtual laboratory-based LKS was able to improve the physics learning outcomes of students in the experimental group with an effect size of 0.804 from the control group. The conclusion of this study shows that virtual laboratory-based LKS has a more effective influence on students' physics learning outcomes and is suitable for use in physics learning